2020
DOI: 10.1159/000517437
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Simple Reaction Time and Balance in Nondemented Parkinson’s Patients

Abstract: <b><i>Background:</i></b> Parkinson’s disease (PD) patients are known to suffer from subtle cognitive and balance deficits from the early stages although they usually manifest in advanced stages. Postural instability (PI) has been correlated with slower information processing speed. Simple reaction time (SRT) tasks can be used to measure the speed of information processing. The main objective of this study was to examine the usefulness of SRT as a valid predictor of balance in PD, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Similarly, recent studies have shown that the combination of physical and cognitive factors is the key to improving response times [44], a very important aspect in frail groups and one, according to some authors, whose deterioration could be related to a greater risk of suffering falls in groups such as those affected by Parkinson's disease [45,46]. Therefore, in future research with IVR, it would be interesting to integrate all of these variables, objectifying physical, cognitive, and response time results in the elderly.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, recent studies have shown that the combination of physical and cognitive factors is the key to improving response times [44], a very important aspect in frail groups and one, according to some authors, whose deterioration could be related to a greater risk of suffering falls in groups such as those affected by Parkinson's disease [45,46]. Therefore, in future research with IVR, it would be interesting to integrate all of these variables, objectifying physical, cognitive, and response time results in the elderly.…”
Section: Discussionmentioning
confidence: 98%